2022
DOI: 10.1177/00221465211066855
|View full text |Cite
|
Sign up to set email alerts
|

Dualized Labor Market and Polarized Health: A Longitudinal Perspective on the Association between Precarious Employment and Mental and Physical Health in Germany

Abstract: This study analyzes the longitudinal association between precarious employment and physical and mental health in a dualized labor market by disaggregating between-employee and within-employee effects and considering mobility in precariousness of employment. Analyses were based on the German Socio-Economic Panel from 2002 to 2018 considering all employees ages 18 to 67 years (n = 38,551). Precariousness of employment was measured as an additive index considering working poverty, nonstandard working time arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 63 publications
1
10
0
3
Order By: Relevance
“…However, the study has some limitations. First, results indicated significant but rather small differences in physical and mental health by working poverty status, especially in comparison to studies with a single-item health outcome [ 5 , 49 ]. Various aspects may have contributed to this.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the study has some limitations. First, results indicated significant but rather small differences in physical and mental health by working poverty status, especially in comparison to studies with a single-item health outcome [ 5 , 49 ]. Various aspects may have contributed to this.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, several authors highlighted that deprivation in living standards results from a prolonged spell of insufficient income when financial savings are exhausted [ 37 ]. Therefore, deprivation might also imply a deep and long-lasting socioeconomic disadvantage over the life course, which contributes to the hypothesis that the working poor differ strongly in their socioeconomic and health situation from other employees [ 5 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A labor market is described as dualized when a group of workers are systematically excluded from regular employment, whereas regular workers are protected from the consequences of market fluctuations. 21 This dualization of labor markets is policy-based and has been institutionalized since the 1980s in various countries such as France, Germany, Italy, the Netherlands, Poland, Portugal, Slovenia, Spain, and Sweden. 72…”
Section: Empirical Findings On the Rise Of Precarious Employment In E...mentioning
confidence: 99%
“…20 Recent studies also point to a consolidation of precarious employment, resulting in a polarization in health between precarious and non-precarious workers. 12,21 The association between precarious employment and health is explained at the individual level by two mechanisms. 3,22 A first explanatory approach considers the physical and psychosocial burdens at the workplace and at the household level of precarious employees as central risks for poorer health.…”
mentioning
confidence: 99%
“…Our understanding of the links between work schedules and sleep and health has also been refined through increasingly sophisticated data, including from small cross-sectional samples [ 12 , 25 ], nationally representative samples [ 1 , 26 ], and panel data [ 27 , 28 ]. For example, using two-year longitudinal data on approximately 1,500 Norweigan nurses, Waage and colleagues found that nurses working night hours the prior year were more likely to report acute sleepiness or insomnia related to shiftwork in the current year [ 27 ].…”
Section: Introductionmentioning
confidence: 99%